Concomitant Immunosuppressive Therapy Use in Eculizumab-Treated Adults With Generalized Myasthenia Gravis During the REGAIN Open-Label Extension Study - Nowak, Richard J.; Muppidi, Srikanth; Beydoun, Said R.; O'Brien, Fanny L.; Yountz, Marcus; Howard, James F. (Frontiers in Neurology, 2020)
Introduction: Chronic, broad-spectrum immunosuppressive therapy (IST) can be associated with side effects in many people with generalized myasthenia gravis (gMG), and treatment guidelines recommend that the IST dose be tapered once patients achieve a stable treatment response. We therefore examined IST use in eculizumab-treated patients with refractory gMG. Methods: The REGAIN open-label extension (OLE) enrolled 117 adults with refractory anti-acetylcholine receptor antibody-positive gMG who had completed the 6-month, randomized, double-blind, placebo-controlled REGAIN study of eculizumab. Eligible patients had received ≥ 2 ISTs for ≥ 1 year, or ≥ 1 IST with intravenous immunoglobulin or plasma exchange ≥ 4 times in 1 year, without symptom control. During REGAIN, changes in concomitant MG therapies were not permitted; during the OLE they were permitted at the investigators’ discretion. Participants received eculizumab 1200 mg every 2 weeks for up to 4 years; concomitant prednisone/related corticosteroids (PRED), azathioprine (AZA), and mycophenolate mofetil (MMF) use was recorded. Changes in MG Activities of Daily Living and Quantitative MG total scores, MG exacerbations and adverse events were also recorded. Results: At last OLE assessment, 88.0% (103/117) of participants were using ≥ 1 IST versus 98.3% (115/117) at OLE baseline. During the OLE, 76.9% (90/117) of patients experienced a total of 719 IST changes. Stopping or decreasing ≥ 1 IST owing to MG symptom improvement was the most common change (38.9% [280/719] of all changes) and occurred in 48.7% [57/117] of participants. In patients who decreased and/or stopped ≥ 1 IST, mean daily doses of PRED, AZA, and MMF decreased between OLE baseline and last assessment by 60.8% (standard deviation [SD], 28.07; P < 0.0001), 89.1% (SD, 25.77; P < 0.0001), and 56.0% (SD, 32.99; P < 0.0001), respectively. Improved clinical outcomes were observed with eculizumab regardless of IST changes during the OLE, and eculizumab’s safety profile was similar in patients who used PRED, AZA, and MMF. Conclusions: Use of ISTs by patients with previously refractory gMG decreased during eculizumab treatment in the REGAIN OLE. Clinical improvements with eculizumab were maintained by patients in all groups, including those who decreased and/or stopped concomitant ISTs. Trial registration: www.clinicaltrials.gov: NCT01997229, NCT02301624.